Is there a difference in 25-hydroxyvitamin D levels between female university students with and without joint hypermobility? - Tuna, Filiz; Özdemir, Hande; Demirbağ Kabayel, Derya; Doğanlar, Zeynep Banu (The European Research Journal, 2019)
Objectives: Individuals with joint hypermobility (JH) constitute a sensitive group with regard to musculoskeletal problems. This study aimed to investigate whether females with generalized joint hypermobility (GJH) are at risk of hypovitaminosis D compared with non-GJH female participants and whether there is a relationship between vitamin D levels, Beighton score and musculoskeletal complaints. Methods: In this cross-sectional, descriptive and case-control study, 76 female participants aged 18-25 years were included. The Beighton score with a cut-off of 4/9 was applied for defining GJH. In addition, serum biochemical (the enzymatic colorimetric method) and hormonal (the electrochemiluminescence method) parameters were evaluated. Results: The mean serum 25-hydroxyvitamin D (25[OH]D) levels of GJH (n = 38) and non-GJH (n = 38) groups were 15.70 ± 7.96 ng/mL and 16.80 ± 5.45 ng/mL, respectively. There was no statistically significant difference between the groups in terms of biochemical and hormonal parameters. We found vitamin D deficiency in 89.5% of participants with GJH, and 84.2% of controls. There was no correlation between vitamin D, Brighton criteria, and musculoskeletal complaints. Conclusion: The female participants with GJH showed similar frequency of musculoskeletal complaints and similar low level of 25(OH)D in relation to controls.